Shear performance of reinforced expansive concrete beams utilizing aluminium waste - Yasin Onuralp Özkılıç; Memduh Karalar; Ceyhun Aksoylu; Alexey N. Beskopylny; Sergey A. Stel'makh; Evgenii M. Shcherban; Shaker Qaidi; Iully da S.A. Pereira; Sergio Neves Monteiro; Afonso R.G. Azevedo (Journal of Materials Research and Technology, 2023)
Shear damage is a catastrophic failure in the design of reinforced concrete structural elements. To prevent it, the effect of aluminum wastes on reinforced concrete shear beams was investigated in this study. There is a gap in the scientific field on the expanding concrete with aluminium waste, and no research has been done on the utilizing of aluminum waste to produce expandable concrete. Moreover, there is a gap in expandable concrete usage with aluminum waste reinforcing, which is crucial for engineering applications especially beams, slabs and columns. For this purpose, experimental investigations were performed on a total of 12 Reinforced Concrete Beams (RCB) with different aluminum waste ratio (0, 1, 2 and 3 vol.%) and different shear reinforcement spacing (270, 200 and 160 mm). The depth span ratio was chosen as 1.6, 2.0 and 2.7. RCB was simply supported on the loading frame and subjected to four-points bending. As a result of experimental tests for each sample, the maximum load, stiffness, ductility and energy dissipation capacity were calculated. It was observed that the load capacity of the Al refuse combined RCBs raises as the vacancy of the stirrup reinforcement reductions compared with reference RCBs. Furthermore, it was found that the load capacity of the RCBs reduced as the Al refuse quantity in the concrete mixture was increased from 0% to 3%. However, it was found that the decrease in load capacity for 1 vol.% aluminum waste could be tolerated. For this reason, it can be stated that aluminum waste (AW) in reinforced concrete shear beams will contribute to the beam up to 1%.